Use of game-based educational entertainment media to foster mathematical problem-solving proficiency in pre-service mathematics teachers - Yulia, Romadiastri; Mujiasih, Mujiasih; Ardani, Riska Ayu; Setambah, Mohd Afifi Bahurudin (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The capacity to solve mathematical problems is an essential component of the professional abilities that pre-service instructors of mathematics are required to possess. When it comes to coping with technological advancements in the sphere of education, this skill serves as the foundation. For the purpose of enhancing one's capacity to solve mathematical problems, this study proposes an innovative method that involves the use of game-based educational entertainment media (GEM). Within the realm of development research, this research technique focuses on the ways in which problem-solving skills can be enhanced by participation in activities that are based on game-based entertainment media. The ADDIE phases—analysis, design, development, implementation, and evaluation—are the steps that are utilised in the process of development. The GEM was utilised by 94 pre-service mathematics teachers who participated in this research. GEM is effective in developing mathematical problem-solving skills, according to the findings of the research. This is accomplished by encouraging pre-service mathematics teachers to identify problems, model them, solve problems mathematically, and assess the results of their efforts.